African amphora contents: an update - (:unkn) unknown (My University, 2021)
This papers aims to update the previous syntheses made by the author in 2004 and 2007 about the contents of African amphorae. Firstly, there is a revision of the different arguments providing information on these contents (typology, epigraphy, distribution, stoppers, macro-remains, archaeometry), and second, an updating of the different hypotheses relating to contents (oil, fish products and wine) by types. The conclusion is that very little progress has been made for 15 years, and the hypotheses about contents can still be divided into three categories: certain (oil for types Africana I and Tripolitana I/III; salsamenta for type Africana II C; wine for imitations of types Dressel 2/4, Gauloise 4 and LRA 1); controversial (amphorae of Punic tradition, early Roman types, Africana II and III); and completely conjectural (5th to 7th century types). The author calls for the launch of an ambitious programme of chemical analyses in order to reach a better understanding of the foodstuffs transported in the African amphorae from the mid 2nd century BC to the end of the 7th century-beginning 8th century AD.
Keywords: African Research